Effects of two different blends of naturally mycotoxin-contaminated maize meal on growth and metabolic profile in replacement heifers. (13th June 2014) - Abeni, F.; Migliorati, L.; Terzano, G. M.; Capelletti, M.; Gallo, A.; Masoero, F.; Pirlo, G.
<x content-type="archive" xml:space="preserve">Abstract</x> The aim of this trial was to assess the effects of the administration of different combinations of mycotoxins in naturally contaminated maize grains on dairy heifer growth, blood measurements and puberty onset. A total of 35 Friesian female heifers were randomly allotted to three experimental groups from 18–21 to 42–45 weeks of age. During the 24-week experimental period (EP), heifers were fed the same diet, but with maize meal derived from three differently contaminated lots: very low contamination, as control (C); medium–low aflatoxin-contaminated (A); and mixed aflatoxin–fumonisin contaminated (A-F). At the end of the EP, they returned to a common diet without contaminated maize, and they were monitored for an additional period of 12 weeks (post-experimental period, PEP). BW, wither height, hip height, body length and heart girth were measured every 4 weeks from the beginning of EP to the end of PEP. At the same time, body condition score was evaluated and blood samples were taken from the jugular vein to be analysed for haematological, serum protein and metabolic profiles. Age at puberty was assessed by measuring weekly plasma progesterone levels from 40 to 52 weeks of age. Body growth measurements were processed both by ANOVA of average daily gain of EP and PEP separately, and by the analysis of growth curve parameters. Haematological, serum protein and metabolic profile were evaluated using a mixed model, taking into account the repeated measurements in time on each animal. Heifers' growth was delayed both in A and A-F groups during EP, as evidenced by the different linear coefficients of the BW growth curve in the three groups. Differently contaminated diets did not affect the haematological profile, so that it can be concluded that these levels of mycotoxin contamination do not determine any specific effect on haematopoiesis and immunity in growing heifers. The main blood marker of mycotoxin chronic toxicity was the γ-glutamyl transferase activity level in plasma, which appeared to be altered even after the removal of mycotoxins. During EP, plasma glucose was lower in the groups fed contaminated diet compared with C. The joint actions of an altered nutritional status and a long-lasting liver damage were probably the causes of the delay in puberty attainment in A and, particularly, in the A-F group. The results from this trial evidenced that a chronic aflatoxin–fumonisin contamination in diets of dairy heifers can determine an important delay in the reproductive career of these animals.